(untitled) (International journal of artificial intelligence, 2025)
Ethnographisms, as linguistic reflections of cultural artifacts, traditions, and social norms, play a significant role in shaping national mentality. This study investigates how ethnographisms contribute to the formation and preservation of collective cultural identity, focusing on examples from Uzbek language and comparing them with select global contexts. The research explores semantic, pragmatic, and symbolic functions of ethnographisms in everyday language and folklore. The findings highlight their role in transmitting cultural values and sustaining national consciousness across generations